A method for measuring the quality of friction skin impression evidence: Method development and validation. (March 2021) - Swofford, H.; Champod, C.; Koertner, A.; Eldridge, H.; Salyards, M.
Highlights: Quality is measured in terms of: Value, Complexity, and Difficulty. Results demonstrate reasonable consistency with experts' subjective judgments. Provides empirical foundations to experts' opinions. Provides an efficient framework for strengthening quality assurance protocols. Abstract: The forensic fingerprint community has faced increasing criticism by scientific and legal commentators, challenging the validity and reliability of fingerprint evidence due to the lack of an empirical basis to assess the quality of the friction ridge impressions. This paper presents a method, developed as a stand-alone software application, DFIQI ("Defense Fingerprint Image Quality Index"), which measures the clarity of friction ridge features (locally) and evaluates the quality of impressions (globally) across three different scales: value, complexity, and difficulty. Performance was evaluated using a variety of datasets, including datasets designed to simulate casework and a dataset derived directly from casework under operational conditions. The results show performance characteristics that are consistent with experts' subjective determinations. This method provides fingerprint experts: (1) a more rigorous approach by providing an empirical foundation to support their subjective determinations from the Analysis phase of the examination methodology, (2) a framework for organizations to establish transparent, measurable, and demonstrable criteria for Value determinations, (3) and a means of flagging impressions that are vulnerable to erroneous outcomes or inconsistency between experts (e.g., higher complexity and difficulty), and (4) a method for quantitatively summarizing the overall quality of impressions for ensuring representative distributions for samples used in research designs, proficiency testing and error rate testing, and other applications by forensic science stakeholders.